RELATIONSHIP BETWEEN DENTAL ANXIETY AND PAIN EXPERIENCE DURING DENTAL EXTRACTIONS - KUMAR MP, SANTHOSH (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To assess the effects of anxiety on pain experienced during dental extractions. Methods: A prospective study was conducted during the academic year July-September 2016, randomly among 60 dental patients who visited the outpatient Department of Oral and Maxillofacial Surgery, Saveetha Dental College, Saveetha University, Chennai, for single tooth extraction. Anxiety was measured using the Hamilton anxiety rating scale. The pain was measured using the pain visual analog scale (VAS) for the level of pain perceived during extraction. Data collected were analyzed with Statistical Package for Social Sciences for Windows, Version 16.0 (SPSS Inc., Chicago, IL, USA) and results obtained. Results: From regression analysis, R2=0.605 which meant that the independent variable (anxiety) explained 60.50% of the variability of the dependent variable (pain) with significant t-value. There was a statistically significant correlation between VAS and total anxiety score (p<0.05). This strongly suggests that an increase in pain level is associated with an increase in anxiety level. Conclusion: Pre-operative dental anxiety is a major predictor of pain experienced by patients during dental extractions. Hence, it is an important to reduce anxiety before treatment to reduce pain during the treatment. Pharmacologic modalities like sedation can be used for reducing anxiety and pain related to the treatment in indicated patients. Keywords: Dental anxiety, Sedation, Anesthesia, Pain, Tooth extraction.